Exchange Rate Developments of Cryptocurrencies Based on Event Study Analysis - Czeczeli, Vivien; Vilonya, Martin (Public Finance Quarterly, 2022)
As the cryptocurrency market dynamically evolves, important financial and economic issues arise. The main focus of the present research is on the price of cryptocurrencies. Following the exploration of the literature base, special emphasis was put on the comparison between the crypto market and markets for different asset classes (gold, stocks, foreign currency) and on the identification of connection points. Next, the article focuses on the period after 2020, and applies the event study methodology in order to establish, how the two cryptocurrencies with the highest market capitalization (Bitcoin and Ethereum) reacted to selected events. These events mainly encompassed hacker attacks aimed at the systems that form the basis of the operation of cryptocurrencies, and also certain steps regarding their regulation and application. Overall, it was established that hacker attacks did not have a significant effect on the exchange rates of the two examined cryptocurrencies. Effects of regulatory action on prices are mixed, however even significant effects can be regarded as short-lived.